Ultralong Phosphorescence of Water-Soluble Organic Nanoparticles for In Vivo Afterglow Imaging - Zhen, Xu (2017)
Afterglow or persistent luminescence eliminates the need for light excitation and thus circumvents the issue of autofluorescence, holding promise for molecular imaging. However, current persistent luminescence agents are rare and limited to inorganic nanoparticles. This study reports the design principle, synthesis, and proof-of-concept application of organic semiconducting nanoparticles (OSNs) with ultralong phosphorescence for in vivo afterglow imaging. The design principle leverages the formation of aggregates through a top-down nanoparticle formulation to greatly stabilize the triplet excited states of a phosphorescent molecule. This prolongs the particle luminesce to the timescale that can be detected by the commercial whole-animal imaging system after removal of external light source. Such ultralong phosphorescent of OSNs is inert to oxygen and can be repeatedly activated, permitting imaging of lymph nodes in living mice with a high signal-to-noise ratio. This study not only introduces the first category of water-soluble ultralong phosphorescence organic nanoparticles but also reveals a universal design principle to prolong the lifetime of phosphorescent molecules to the level that can be effective for molecular imaging.